2022
DOI: 10.1177/03635465221090902
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Arthroscopic Anterior Labroligamentous Periosteal Sleeve Avulsion Lesions: A Minimum 2-Year Follow-up

Abstract: Background: Anterior labroligamentous periosteal sleeve avulsion (ALPSA) lesions can occur in recurrent anterior shoulder instability, which may lead to the labrum scarring medially to the glenoid. ALPSA lesions have also been associated with greater preoperative dislocations, larger Hill-Sachs lesions, and greater degrees of glenoid bone loss. Therefore, patients with these lesions have historically had a higher failure rate after repair, with nearly double the recurrent instability rate compared with those u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…1 However, two of the studies included in this review found higher rates of recurrence in ALPSA patient groups as compared to isolated Bankart groups. 4,7 rence rates, physicians likely continue to perform arthroscopic ALPSA repairs due to the high frequency of preoperative dislocations in patients with ALPSA lesions, which was cited as over 12 dislocations per patient in one study. 6 It should be noted however that the studies included in this review span nearly 30 years, during which time arthroscopic techniques have improved and different approaches to ALPSA repair have been developed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 However, two of the studies included in this review found higher rates of recurrence in ALPSA patient groups as compared to isolated Bankart groups. 4,7 rence rates, physicians likely continue to perform arthroscopic ALPSA repairs due to the high frequency of preoperative dislocations in patients with ALPSA lesions, which was cited as over 12 dislocations per patient in one study. 6 It should be noted however that the studies included in this review span nearly 30 years, during which time arthroscopic techniques have improved and different approaches to ALPSA repair have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…8 METHODOLOGICAL ASSESSMENT AND RISK OF BIAS Two blind reviewers (CR, CN) evaluated included studies for methodological quality and risk of bias according to the JBI Clinical Appraisal tools for cohort studies, case series, and case reports, respectively. Two cohort studies 4,6 had a mean score of 10.5 out of 11. Three case series 3,7,10 scored a mean of 9.3 out of 10 and one case report 11 scored an 8 out of 8.…”
Section: Literature Search and Screeningmentioning
confidence: 99%
See 3 more Smart Citations